Retrospective assessment of adverse drug reactions linked to first-line antituberculosis drugs at a tertiary healthcare facility in Northern India - Kumar, Abhinandan; Yadav, Ritu; Chaurasia, Rakesh Chandra (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Tuberculosis (TB) continues to pose a major health challenge in India, where the burden remains among the highest globally. First-line anti-tubercular therapy (ATT), though effective, often leads to adverse drug reactions (ADRs) that may interfere with patient adherence and overall treatment success. This study aimed to assess the pattern and severity of ADRs associated with ATT in a real-world clinical setting. Methods: This retrospective review analyzed 102 reports of adverse drug reactions (ADRs) submitted to the Pharmacovigilance Programme of India (PvPI). Data were obtained from the ADR Monitoring Centre at Motilal Nehru Medical College, Prayagraj. Although the data were collected between 2015 and 2018, the analysis was performed in 2025 to derive retrospective insights into ADR trends. Given the consistency of the standard ATT regimen over the years, the findings remain clinically relevant. The study evaluated types of ADRs, severity using the modified Hartwig and Siegel scale, and causality using WHO-UMC criteria. Statistical analysis was performed using SPSS version 25. Results: Drug-induced hepatitis was the most frequently observed ADR (58.8%), followed by gastrointestinal symptoms (22.5%) and skin-related reactions (8.8%). Most ADRs occurred in male patients (63.7%) and during the intensive phase of ATT (73.5%). A significant correlation was noted between the type of ADR and the treatment phase (chi-square =56.29; p<0.001). Conclusions: ADRs with first-line ATT are not uncommon, with liver toxicity being especially prevalent during the initial months of treatment. Strengthening ADR monitoring and early intervention can help improve treatment adherence and patient safety.